2015
DOI: 10.1016/j.chemgeo.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tungstate polymerization on tungsten(VI) adsorption on ferrihydrite

Abstract: Tungsten (W) is expected to adsorb to soil minerals, but does not appear to do so in many environments. To explain this behavior, adsorption experiments were performed over a variety of W(VI) solution compositions with different extents of W polymerization, on ferrihydrite. Tungsten adsorption was more extensive at circumneutral pHs and in systems with lower W(VI) concentrations, conditions under which tungstate rather than polytungstate was stable or the transformation to polytungstates was inhibited. Polytun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 42 publications
1
30
1
Order By: Relevance
“…Literature data reveal, that removal of tungstate using popular sorbents such as gibbsite, goethite or birnessite was significantly lower than the results obtained in this study (201, 174 and 24 mmol/kg, respectively) [4,7]. Previous studies also show, that for some sorbents, such as ferrihydrite, the sorption capacities obtained by different researchers differ significantly, form 120 mmol/kg to 420 mmol/kg [7,48]. It was observed that popular sorbents are also less effective than organically modified montmorillonite.…”
Section: Discussioncontrasting
confidence: 49%
“…Literature data reveal, that removal of tungstate using popular sorbents such as gibbsite, goethite or birnessite was significantly lower than the results obtained in this study (201, 174 and 24 mmol/kg, respectively) [4,7]. Previous studies also show, that for some sorbents, such as ferrihydrite, the sorption capacities obtained by different researchers differ significantly, form 120 mmol/kg to 420 mmol/kg [7,48]. It was observed that popular sorbents are also less effective than organically modified montmorillonite.…”
Section: Discussioncontrasting
confidence: 49%
“…One possible fate of added W (VI) is sorption by soil minerals. Consequently, many studies evaluated the sorption mechanisms of W (VI) on various soil minerals (Gustafsson, 2003;Xu et al, 2006Xu et al, , 2009Lorenz, 2009;Lorenz et al, 2011;Kashiwabara et al, 2013;Davantes and Lefevre, 2015;Sun and Bostick, 2015;Hur and Reeder, 2016;Rakshit et al, 2017). In general, W (VI) displays a high affinity for iron-and aluminum hydr (oxide) minerals (Gustafsson, 2003;Xu et al, 2009;Hur and Reeder, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Kashiwabara et al [20] found that W shows a much larger adsorption on ferrihydrite than Mo. Sun and Bostick [21] examined that aqueous W speciation is of critical importance for regulating W adsorption on ferrihydrite. It is suggested that polyoxytungstates and heteropolytungstates adsorb to a lesser degree than tungstate onto ferrihydrite and presumably other minerals.…”
Section: The Role Of Iron Oxidesmentioning
confidence: 99%